A Practical High‐Energy Cathode for Sodium‐Ion Batteries Based on Uniform P2‐Na0.7CoO2 Microspheres. (25th April 2017) - Fang, Yongjin; Yu, Xin‐Yao; Lou, Xiong Wen (David)
Abstract: Layered metal oxides have attracted increasing attention as cathode materials for sodium‐ion batteries (SIBs). However, the application of such cathode materials is still hindered by their poor rate capability and cycling stability. Here, a facile self‐templated strategy is developed to synthesize uniform P2‐Na0.7 CoO2 microspheres. Due to the unique microsphere structure, the contact area of the active material with electrolyte is minimized. As expected, the P2‐Na0.7 CoO2 microspheres exhibit enhanced electrochemical performance for sodium storage in terms of high reversible capacity (125 mAh g −1 at 5 mA g −1 ), superior rate capability and long cycle life (86 % capacity retention over 300 cycles). Importantly, the synthesis method can be easily extended to synthesize other layered metal oxide (P2‐Na0.7 MnO2 and O3‐NaFeO2 ) microspheres.